The compliance to pay zakat on gold: a study on muslim woman staff in UiTM Johor / Muhamad Amirul Hakim Mazlan - Mazlan, Muhamad Amirul Hakim (Faculty of Business Management, 2017)
The objective of this research is to examine the relationship between factors that influence the compliance to pay zakat on gold among Muslim woman staff in Universiti Teknologi Mara (UiTM), Johor. The independent variables of the study are the attitude, religious value, knowledge in zakat, and law of zakat and compliance to pay zakat on gold as dependent variable. The questionnaire is distributed to 105 respondents of Muslim woman staff in Universiti Teknologi Mara (UiTM), Johor, Campus Segamat. In this study, the researchers use the previous study's construct in measuring the compliance to pay zakat on gold, attitude, religious value, knowledge on zakat, and law of zakat. This study is using quota sampling technique which means the subjects are convenience chosen. Other than that, a quantitative method and primary data are using to collect the data through questionnaire and secondary data source which are journals and articles. The data collected will be analysing by using Statistical Package of Social Sciences (SPSS) version 2.1. The multiple regression analysis is use to analyse a significant and positive impact of the independent variables on compliance to pay zakat on gold. The findings show that attitude has a very high significant and positive correlation with the compliance to pay zakat on gold followed by knowledge on zakat. The result of the study may improve the effectiveness of the zakat collection especially zakat on gold.